Material challenges for solar cells in the twenty-first century: directions in emerging technologies. Issue 1 (31st December 2018) - Almosni, Samy; Delamarre, Amaury; Jehl, Zacharie; Suchet, Daniel; Cojocaru, Ludmila; Giteau, Maxime; Behaghel, Benoit; Julian, Anatole; Ibrahim, Camille; Tatry, Léa; Wang, Haibin; Kubo, Takaya; et al.
Abstract: Photovoltaic generation has stepped up within the last decade from outsider status to one of the important contributors of the ongoing energy transition, with about 1.7% of world electricity provided by solar cells. Progress in materials and production processes has played an important part in this development. Yet, there are many challenges before photovoltaics could provide clean, abundant, and cheap energy. Here, we review this research direction, with a focus on the results obtained within a Japan–French cooperation program, NextPV, working on promising solar cell technologies. The cooperation was focused on efficient photovoltaic devices, such as multijunction, ultrathin, intermediate band, and hot-carrier solar cells, and on printable solar cell materials such as colloidal quantum dots. Abstract :